Faculty Support for High-Impact Study Abroad Experiences: A Community of Practice Model - Cicchino, Amy; Clevenger, Aaron; Macchiarella, Sue (Experiential Learning and Teaching in Higher Education, 2025)
This qualitative study identifies impacts a community of practice program had on faculty-participants leading study abroad learning experiences. Through qualitative analysis of learning artifacts and interviews, researchers highlight that a professional development program focused on cultural competence and high impact practices (HIPs) frameworks led faculty to think about curriculum, planning, and assessment in new ways, balancing logistical and theoretical trip design. Specifically, participant data showed the program offered a theoretical language and framework, challenged assumptions about study abroad as a vacation-like trip, and encouraged faculty to develop assessment mechanisms for cultural competence in addition to their course learning outcomes. Despite limitations in participant sample size and the single institutional context of this study, these data raise important questions about how faculty are prepared to instruct and lead study abroad and other HIPs, and how cross-campus partnerships can foster more comprehensive professional development opportunities in these areas.